Pemanfaatan Media Koran untuk Meningkatkan Kemampuan Writing Peserta Didik Kelas XII SMK Negeri 3 Pamekasan dalam Membuat Teks News Item - Dinar Vincy Yunitaka B; Fitrah Yuliawati (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
Students writing mastery in English skill become a big problem that faced by Indonesian students, where is English as a foreign language for them. In order to overcome this problem, writing training was held by utilizing newspaper media. This training held in SMKN 3 Pamekasan specifically for students at XII grade. Writing news item text training give positif impact in increasing students writing ability. It is prove by students writing result that is in accordance with the generic structure of news item and also the correct use of the language. The students were very interested and enjoyed in making the news item text. There were no difficulties which become a barries or obstacles for students to make written work. From the explanation above it can be concluded that writing training by using newpaper as a media is very effective and efficent in increasing students’ news item ability.